Colon cancer metastasis mimicking a hilar cholangiocarcinoma: a case report and literature review - Takashi Ofuchi; Hiromitsu Hayashi; Takanobu Yamao; Takaaki Higashi; Toru Takematsu; Yosuke Nakao; Kensuke Yamamura; Katsunori Imai; Yo-ichi Yamashita; Hideo Baba (Surgical Case Reports, 2020)
Abstract Background An accurate diagnosis of the primary cancer or metastatic tumor is quite important because misdiagnosis may lead to the selection of incorrect adjuvant therapy and worse long-term outcomes after surgery. Here, we present a rare case with an unusual metastatic pattern mimicking a hilar cholangiocarcinoma originated from colon cancer Case presentation A 69-year-old man was referred to our hospital because of an upper bile duct stenosis. He had the past history of the sigmoidectomy for the primary colon cancer and the partial hepatectomy with radiofrequency ablation (RFA) for synchronous liver metastases 4 years ago. After 2 years from the initial operation, he had experienced the local recurrence of post-RFA lesion and had undergone a partial hepatectomy. According to the radiological findings of the bile duct stenosis, we diagnosed a hilar cholangiocarcinoma (Bismuth type II), and then he underwent the extended right hepatectomy with extrahepatic bile duct resection. Histological findings including the immune-histochemical examinations (CK7−, CK20+, CDX2+ and SATB2+) uncovered the metastatic tumor into extrahepatic bile duct originated from the primary colon cancer. Conclusion We experienced an extremely rare case with a colon cancer metastasis mimicking a hilar cholangiocarcinoma. In this case with a past history of colon cancer, an immunohistochemical staining led us to distinguish the primary hilar cholangiocarcinoma and the mimicking tumor.